Hubungan Pengetahuan, Sikap dan Tindakan dengan Kepatuhan Mengonsumsi Tablet Fe pada Remaja Putri di SMAN 1 Kabangka Kabupaten Muna - Wa Ode Putri Wahyuni; Asnia Zainuddin; Ruwiah Ruwiah (Universitas Pahlawan Tuanku Tambusai, 2023)
Fe tablets are folate iron tablets, each containing 200 mg of ferro sulfate, 60 mg of elemental iron, and 0.25 mg of folic acid. Anemia is a condition in which hemoglobin (Hb) levels in the blood are lower than normal. Factors that can affect the consumption of Fe tablets in teenage daughters, namely lack of knowledge about nutrition, attitudes toward irregular dietary patterns, and inappropriate actions to take the Fe tablet The purpose of this research is to find out the relationship between knowledge, attitudes, and actions and compliance with the consumption of Fe tablets in the SMAN 1 Kabangka district of Muna. This type of research is observational, with a cross-sectional design. The sample in this study was 145 teenage girls in classes X, XI, and XII. The data is then processed and analyzed using the Chi Square Test. The results of this research show that there is a relationship between knowledge and compliance with the consumption of tablets. Fe in SMAN 1 Kabangka district of Muna (p = 0,003), there is no relationship between the attitude of young girls and compliance with taking tablets Fe in SMAN 1 Kabangka district (p = 0,244), and there is a connection between the actions of teenage daughters and compliance using tablets Fe in SMAN 1 Kabangka district of Muna (p = 0,006). It is hoped that the puskesmas can provide an understanding of the importance of taking Fe tablets for teenage daughters to prevent anemia as well as multiply the distribution of Fe tablets to schools. Keywords: knowledge, attitudes, actions, Fe tablets